Zanubrutinib in lymphoproliferative disorders: a comprehensive review - Javier Muñoz; Yucai Wang; Preetesh Jain; Michael Wang (Therapeutic Advances in Hematology, 2022)
The availability of Bruton tyrosine kinase (BTK) inhibitors has brought about a paradigm shift in the treatment of patients with B-cell lymphomas and chronic lymphocytic leukemia. BTK was clinically validated as a target by the efficacy of the first-in-class inhibitor ibrutinib. The extended survival conferred by BTK inhibitors has brought long-term tolerability to the foreground. To minimize toxicities thought to be attributable to off-target kinase inhibition, a next generation of BTK inhibitors with greater selectivity was developed. In the United States, zanubrutinib, a next-generation BTK inhibitor, has been approved for treating adults with mantle cell lymphoma who have received at least one prior therapy, for adults with Waldenström macroglobulinemia, and for adults with relapsed or refractory marginal zone lymphoma who have received at least one anti-CD20–based therapy. Because few head-to-head comparative trials of BTK inhibitors have so far been reported, no BTK ‘inhibitor of choice’ can be identified. Zanubrutinib has promising efficacy in its approved indications and appears to have reduced cardiac toxicities, particularly atrial fibrillation, which may influence the choice of BTK inhibitor treatment by prescribers. Further studies are needed to inform on optimal treatment sequencing of zanubrutinib and its combination with other agents. Here, we summarize existing clinical evidence for its efficacy and safety in mantle cell lymphoma, Waldenström macroglobulinemia, marginal zone lymphoma, chronic lymphocytic leukemia/small lymphocytic lymphoma, and other B-lymphoproliferative indications. Plain Language Summary Zanubrutinib is a drug that was shown to effectively treat cancer of B cells without causing excessive serious side effects Patients with certain B-cell malignancies (cancers of white blood cells) benefit from treatment with Bruton tyrosine kinase (BTK) inhibitors, drugs that block the BTK protein and keep cancer from growing and spreading. Patients experience extended survival with ibrutinib, the first-generation BTK inhibitor approved by US Food and Drug Administration (FDA); however, one in five patients quit treatment because of harmful side effects. Ibrutinib-related side effects such as increased risk of bleeding, atrial fibrillation (abnormal heart rhythm), and high blood pressure are thought to be caused by ibrutinib blocking other proteins besides the intended target protein BTK. To reduce these side effects, zanubrutinib, a next-generation BTK inhibitor, was designed to block BTK more specifically than ibrutinib. Results of clinical studies on zanubrutinib treatment appear promising in patients with several types of B-cell malignancies, including mantle cell lymphoma (MCL), Waldenström macroglobulinemia (WM), marginal zone lymphoma (MZL), chronic lymphocytic leukemia, and small lymphocytic lymphoma. There are not yet enough clinical data to determine which BTK inhibitor is most effective in treating B-cell malignancies without causing harmful side effects. Early data from the phase 3 ALPINE clinical study suggest that zanubrutinib works better than ibrutinib, and fewer patients experience side effects and quit treatment. Zanubrutinib is currently approved for use for treatment of adult patients with MCL who have received at least one prior therapy, for adults with WM, and for adults with MZL who have received at least one anti-CD20–based therapy.